Measuring Financial Sustainability: The Influence of ROA, BOPO, and NIM on Foreign Exchange National Private Commercial Banks in Indonesia - Muis, Muhammad Abdul; Nurdin, M. (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to analyze the influenceReturn on Assets(ROA), Operating Costs to Operating Income (BOPO) andNet Interest Margin(NIM) againstFinancial Sustainability Ratio(FSR) at National Private Commercial Banks for Foreign Exchange in Indonesia during the period 2018 to 2022. The population in this research is all National Private Commercial Banks for Foreign Exchange in Indonesia during the period 2018 to 2022. The sample selection technique used purposive sampling and 15 banks were selected as research data. . The data analysis method used is panel data regression analysis using Eviews 10. The research results show that: Return on Assets (ROA) has a positive and significant effect on the Financial Sustainability Ratio (FSR). Operational Costs on Operating Income (BOPO) and Net Interest Margin (NIM) have a negative and significant effect on the Financial Sustainability Ratio (FSR). The R Square value is 0.957730, indicating that the Financial Sustainability Ratio (FSR) is influenced by Return on Assets (ROA), Operational Costs to Operating Income (BOPO) and Net Interest Margin (NIM) of 95.77%.